2010
DOI: 10.1029/2010eo220001
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Drilling Into the San Andreas Fault Zone

Abstract: This year, the world has faced energetic and destructive earthquakes almost every month. In January, an M = 7.0 event rocked Haiti, killing an estimated 230,000 people. In February, an M = 8.8 earthquake and tsunami claimed over 500 lives and caused billions of dollars of damage in Chile. Fatal earthquakes also occurred in Turkey in March and in China and Mexico in April.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 25 publications
3
116
0
3
Order By: Relevance
“…One possibility is a greatly reduced effective normal stress eff due to the presence of near-lithostatic pore fluid pressure within fault zones [Byerlee, 1990;Rice, 1992;Faulkner and Rutter, 2001]. That explanation does not seem likely, at least for crustal faults, as measurements of pore pressure within Earth's crust generally indicate hydrostatic conditions [Townend and Zoback, 2000], even in the SAF itself [Zoback et al, 2010]. Other theories appeal to anomalously low frictional resistance, from either frictionally weak clayrich materials [Morrow et al, 2000;Carpenter et al, 2011] or weak fault zone fabrics [Collettini et al, 2009] at seismogenic depths.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is a greatly reduced effective normal stress eff due to the presence of near-lithostatic pore fluid pressure within fault zones [Byerlee, 1990;Rice, 1992;Faulkner and Rutter, 2001]. That explanation does not seem likely, at least for crustal faults, as measurements of pore pressure within Earth's crust generally indicate hydrostatic conditions [Townend and Zoback, 2000], even in the SAF itself [Zoback et al, 2010]. Other theories appeal to anomalously low frictional resistance, from either frictionally weak clayrich materials [Morrow et al, 2000;Carpenter et al, 2011] or weak fault zone fabrics [Collettini et al, 2009] at seismogenic depths.…”
Section: Introductionmentioning
confidence: 99%
“…The wider fault gouges of the SAF are likely caused by the cumulative displacement, which is much greater along the SAF than along the Chelungpu fault (Zoback et al, 2010).…”
Section: Structural Setting Of Safod and Tcdp Samplesmentioning
confidence: 99%
“…The main drill hole crosscuts multiple faults including two actively creeping strands, the Southwest Deforming Zone (SDZ) and the Central Deforming Zone (CDZ) (Fig. 1b;Zoback et al, 2010), which were revealed by pronounced and ongoing casing deformation (Bradbury et al, 2007;Zoback et al, 2010). Detailed descriptions of SAFOD Phase 3 core material from Holes E and G (Fig.…”
Section: The Safod Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…During Phase 3 the SAFOD engineering and science teams successfully exhumed 39.9 meters of 10-cm-diameter continuous core, including cores from the two actively deforming traces of San Andreas Fault Zone (the SDZ and CDZ; Zoback et al, 2010). Figure 5 shows the sidetracks drilled laterally off the SAFOD main borehole in map and cross-sectional views.…”
Section: Phase 3 -Coring the San Andreas Fault Zonementioning
confidence: 99%